Process Optimization of Acid Gas Incinerators: Balancing SO₂ Yield and SO₃ Suppression - Ihzantini, Opit; Adhi, Tri Partono (ITB Graduate School Conference, 2025)
In natural gas processing, hydrogen sulfide (H₂S) is a common impurity known for its acidic and toxic properties. This compound is typically converted into sulfur dioxide (SO₂), which serves as a precursor for sulfuric acid production. The conversion process takes place in an Acid Gas Incinerator (AGI), where H₂S reacts with air to form SO₂. However, a side reaction between SO₂ and excess oxygen (O₂) can lead to the formation of sulfur trioxide (SO₃), an undesirable byproduct that can contribute to corrosion and environmental concerns. This study evaluates the performance of the AGI, focusing on maximizing SO₂ production while minimizing SO₃ formation. The simulation is conducted using Aspen HYSYS, employing the SRK-Twu thermodynamic model to accurately represent reaction kinetics and phase behavior. Results indicate that air preheating enhances incinerator performance by improving combustion efficiency and reducing fuel gas demand. Sensitivity analysis reveals that SO₂ and SO₃ yields are significantly influenced by Acid Gas-to-Air Ratio (AAGR), Fuel Gas-to-Acid Gas Ratio (FGAGR), and operating temperature. Optimal performance is achieved when the FGAGR-to-AAGR ratio is maintained within the range of 0.45 to 0.7, ensuring efficient SO₂ conversion while suppressing SO₃ formation.